Kapabilitas Kompi Zeni Nubika TNI AD Dalam Menghadapi Ancaman Bencana Nubika - Hidayat, Fikih (Republic of Indonesia Defense University, 2019)
Weapons of Mass Destruction (WMD) which consist of Nuclear, Biological and Chemical (NBC) are becoming prominent issue in the world, especially after biological and chemical terrorism revealed to the face. Based on the development and the use of NBC weapon, by making an NBC Unit, Indonesian Army constantly alert to the possible impact of the danger of NBC weapons. The unit is prepared well dealing with the threats. The research aims to analyse capabilities of Army NBC Unit dealing with the threats of NBC disaster and their barriers and how to improve those capabilities. This research applied qualitative method by interviews, observation, and secondary data. The results showed that the capability of Army NBC Unit is inadequate from the aspect of human resources, equipments, and budget, making its utilization not optimal. To improve the capability of Army NBC Unit takes efforts to improve human resources, equipment, infrastructure and education. The special abilities of Army NBC Unit can be utilized for disaster prevention of accidents or natural disasters. While the increasing threat of NBC disaster in peace condition, it is suggested to establish battalion-level unit supporting Army NBC unit to be able handling more than two trouble spots in the field.